2021
DOI: 10.1007/s00395-021-00846-y
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα1 deletion in myofibroblasts exacerbates post-myocardial infarction fibrosis by a connexin 43 mechanism

Abstract: We have previously demonstrated that systemic AMP-activated protein kinase α1 (AMPKα1) invalidation enhanced adverse LV remodelling by increasing fibroblast proliferation, while myodifferentiation and scar maturation were impaired. We thus hypothesised that fibroblastic AMPKα1 was a key signalling element in regulating fibrosis in the infarcted myocardium and an attractive target for therapeutic intervention. The present study investigates the effects of myofibroblast (MF)-specific deletion of AMPKα1 on left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“… 7 The massive deposition of ECM and the decrease in the degradation of ECM lead to an imbalance and disturbance of the collagen structure, which eventually leads to MF. 11 The imbalance of MMP and excessive secretion of cytokines such as TGF-β eventually leads to MF. 54 , 55 It has been shown that the upregulation of MMPs after MI leads to a reduction in myocardial tissue thickness (thinning of the ventricular wall), which ultimately leads to deterioration of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The massive deposition of ECM and the decrease in the degradation of ECM lead to an imbalance and disturbance of the collagen structure, which eventually leads to MF. 11 The imbalance of MMP and excessive secretion of cytokines such as TGF-β eventually leads to MF. 54 , 55 It has been shown that the upregulation of MMPs after MI leads to a reduction in myocardial tissue thickness (thinning of the ventricular wall), which ultimately leads to deterioration of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AMPKα1 is a key molecule through which macrophages promote angiogenesis and tissue repair under normoxia and that the depletion of AMPKα1 impairs macrophage promotion of arteriogenesis 40 . AMPKα1 in fibroblasts was reported to function as a master regulator of cardiac fibrosis and remodeling after MI 41 . However, there have only been a few reports on the role of AMPKα2 in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been reported that gap junction alteration in NMCs contributes to promoting arrhythmic events and adverse ventricular remodelling after myocardial infarction [ 11 ]. In addition, the downregulation of cardiac connexins can likewise trigger fibrosis [ 48 , 49 , 50 , 51 ]. Indeed, Cx43 downregulation and the consequent atrial gap junction interruption that characterise the atrial fibrillation condition are associated with an increase in fibrosis, which, in turn, further promotes conduction impairment and re-entry phenomenon development [ 25 ].…”
Section: Discussionmentioning
confidence: 99%